Preventing nipple pain/trauma in breastfeeding women: a best practice implementation project at the Marqués de Valdecilla University Hospital (Spain). Issue 4 (14th December 2022) - Cornejo-del Río, Elsa; Cobo-Sánchez, José Luis; Mateo-Sota, Sonia; Lasarte-Oria, Lorena; Sáez de Adana-Herrero, María; Gortázar-Arias, Pilar; Gómez-Pérez, Tamara; Sainz-Gómez, Gema; Lechosa-Muñiz, Carolina
ABSTRACT: Objectives: To assess compliance with recommendations to alleviate nipple pain and/or trauma (NPT) and to reduce the rate of breastfeeding abandonment for this reason. Introduction: As a fundamental priority, health programmes encourage mothers to breastfeed exclusively for the first 6 months of the baby's life and to supplement breast milk with other foods up to the age of 2 years. However, the presence of NPT can reduce or prevent compliance with this recommendation. Methods: The project was designed and carried out using a framework based on the JBI Practical Application of Clinical Evidence System (JBI-PACES). Six audit criteria were used in preaudits and postaudits to observe any changes in compliance with the recommendations. Between audits, the Getting Research into Practice (GRiP) tool was used to identify stakeholders, barriers and facilitators of the project. Results: Two hundred and sixty-seven breastfeeding women were studied in the baseline phase and 275 during follow-up. Compliance in four criteria improved, and the rates of NPT decreased (pain: from 63.3 to 53.5%; P  = 0.02; trauma: from 37.8 to 24.7%; P  = 0.01). The proportion of women advised by qualified personnel increased from 63 to 88% whereas those who cited pain as the reason for abandoning exclusive breastfeeding decreased from 1.5 to 1.1%. Conclusion: This evidence-based implementation project achieved significantly improved compliance rates in most of the evidence-based criteria considered. In consequence, the prevalence of NPT fell significantly. Nevertheless, there was no significant impact on the proportion of mothers abandoning breastfeeding for this reason.